Actividad antibacteriana in vitro del aceite esencial de piper angustifolium (matico) sobre cepas de staphylococcus aureus meticilino resistente y pseudomonas aeruginosa - Chuquimango Fuentes, Sandra Pamela (2017)
To evaluate the in vitro antibacterial effect of essential oil of Piper angustifolium (Matico) on strains of methicillin resistant Staphylococcus aureus and Pseudomonas aeruginosa. MATERIALS AND METHODS: Experimental study of the antibacterial effect of concentrations of 25%, 50%, 75% and 100% of the essential oil of Piper angustifolium (Matico) on strains of Staphylococcus aureus methicillin resistant and Pseudomonas aeruginosa was used as control Vancomycin 500 mg for methicillin-resistant Staphylococcus aureus and Imipenem 500 mg for Pseudomonas aeruginosa. Disc diffusion method and minimal inhibitory concentration (MIC) were used. The Kruskal-Wallis nonparametric variance analysis test and the paired comparison test were performed using homogeneous subsets. Both with a level of significance P <0.05. Results: Piper angustifolium showed antibacterial activity on methicillin-resistant Staphylococcus aureus with a MIC of 100 % the CFU count was 0 in which concentration of 75% had an inhibition halo of 20.1 ± 4 mm / ml and on Pseudomonas aeruginosa with a MIC of 75 % the CFU count was 0 in Whose concentration of 100% had a inhibition halo of 16.8 ± 1.4 mm / ml. Conclusions: The essential oil of Piper angustifolium (Matico) has an "in vitro" antibacterial effect on strains of methicillin resistant Staphylococcus aureus and Pseudomonas aeruginosa